Penggunaan Media Sosial Youtube dan Wawasan Kebangsaan Mahasiswa Universitas Riau - Siregar, Widia Friliska; Arianto, Jumili; Hariyanti, Hariyanti; Primahadi, Indra (Journal of Civic Education, 2023)
This study was conducted in 2023 with the aim of assessing the influence of YouTube usage on the development of national insight among students at Riau University. The diverse array of content on YouTube pertaining to national insight necessitates careful filtration for subsequent utilization. A total of 268 students participated in this research, and data collection was carried out through the administration of questionnaires and documentation analysis. Quantitative analysis techniques, employing a simple linear regression formula, were employed for data processing.The research findings revealed that the utilization of YouTube at Riau University is at a notably high level, accounting for 78.65% of students. Furthermore, students' national insight also demonstrated a very favorable level. The independent variable, YouTube Social Media, was found to have a substantial influence on students' national insight, accounting for 23.2% of the variance. It is worth noting that other factors, such as student engagement and the individual understanding of national insight, may be influenced by variables not explicitly addressed in this study.